Kebijakan Pembangunan Sarana Prasarana Melalui Dana SBSN di Madrasah - Nasta'in (LP. Ma'arif Janggan Magetan, 2022)
This study aims to describe the policy of developing facilities and infrastructure through SBSN funds in madrasas. The research method used is qualitative with a literature study model. The research data is in the form of literature related to madrasas that carry out infrastructure development programs with SBSN which are accessed from various sources. The data collection technique is done by documentation. The results of the study show that first, the scheme for submitting the construction of madrasa infrastructure through SBSN is easily accessible and carried out by madrasas in Indonesia. Second, the implementation of infrastructure development policies through SBSN funds in madrasas can run smoothly despite many obstacles. Third, the benefits of infrastructure development policies through SBSN funds in madrasas are felt directly by the community. Madrasah infrastructure facilities are no longer left behind and inadequate, thus supporting the achievement of educational goals. Fourth, the impact of infrastructure development policies through SBSN funds in madrasas is to increase public trust and the confidence of madrasa residents.